A Case Report on Unilateral Non-axial Proptosis of a Young Female: Lacrimal Gland Tumour - Bohara, Dikshya; Shrestha, Gulshan Bahadur; Shrestha, Bhupendra Man Singh (Nepalese Journal of Ophthalmology, 2023)
Background: Lacrimal gland adenoma is a benign tumour of the lacrimal gland mostly involving the orbital part of the gland and composed of epithelial and myoepithelial components. It involves the third and fourth decade of life as a gradual painless enlargement of the lacrimal gland. Case: This is a case report of a 30-year-old female presenting with the forward bulging of the right eye causing the eye to be displaced medio-inferiorly over the course of one year. After careful clinical examination and MRI, a clinical diagnosis of lacrimal gland adenoma was established and was planned for right lateral orbitotomy (without marginotomy) via eyelid crease incision and transcutaneous-transseptal approach with complete excision of the tumour under general anaesthesia. Observations: This case was presented to the out patient department with mild painful non-axial proptosis of the right eye. After clinical examination, her MRI report showed a well-defined altered signal intensity enhancing lesion on the extraconal compartment of the right orbit in the antero-supero-lateral aspect. After complete surgical removal of the mass, it was sent for histopathological analysis and it confirmed it as a pleomorphic adenoma. The patient has been following up every 6 months for 2 years and is asymptomatic. Conclusion: Being the most prevalent lacrimal gland tumour, pleomorphic adenoma affects the unilateral lacrimal gland causing non-axial proptosis. Complete removal of mass has an excellent prognosis with complete resolution of symptoms.